The HYdrocortisone for Bronchopulmonary Dysplasia Respiratory and Developmental (HYBRiD) outcomes study: protocol for a longitudinal cohort study - Sara B. DeMauro; Haresh Kirpalani; Kristina Ziolkowski; Susan Hintz; Kristi Watterberg; Jean Lowe; Seetha Shankaran; Sanjay Chawla; Betty Vohr; Michael Msall; Carl D'Angio; Bradley A. Yoder; et al. (BMC, 2024)
Abstract Background Bronchopulmonary dysplasia (BPD) affects up to half of extremely preterm infants, and is associated with adverse long-term respiratory, neurodevelopmental, and educational sequelae and costly health service and family economic outcomes. The NICHD Neonatal Research Network Hydrocortisone for Bronchopulmonary Dysplasia (BPD) Trial evaluated the efficacy and safety of hydrocortisone treatment to prevent BPD in high-risk infants. The trial enrolled 800 very preterm infants with respiratory failure and followed the participants until 2 years corrected age to assess safety of the trial intervention. Longer-term impacts of hydrocortisone exposure and severity of BPD on functional outcomes of high-risk infants remain unknown. The HYdrocortisone for BPD Respiratory and Developmental (HYBRiD) Outcomes Study extends follow-up of all surviving children enrolled in the Hydrocortisone for BPD Trial until early school age. It aims to characterize the childhood functional motor, cognitive, academic, and pulmonary outcomes of this large, well-phenotyped trial cohort. Methods Parents of surviving trial participants complete telephone questionnaires when their children are 3 and 4 years corrected age. A single in-person study visit takes place at early school age (5 years, 0 months to 7 years, 11 months corrected age). Children undergo a multidimensional assessment of functional outcomes and parents complete a battery of questionnaires. In 5 of 19 participating centers, respiratory mechanics are evaluated with impulse oscillometry. Discussion The HYBRiD Outcomes Study will be the largest and most comprehensive evaluation to date of the functional early school age outcomes of children with a history of severe neonatal lung disease and of children exposed to HC during infancy. This will substantially improve understanding of the longer-term implications of severe neonatal lung disease; provide data to facilitate the development of future randomized intervention trials in this population; and inform public policy by enhancing knowledge about school age resource requirements in children with a history of prematurity and lung disease. Trial registration clinicaltrials.gov ID NCT01353313. Primary trial registration 5/11/11 modified to include followup through school age 12/13/17. This manuscript reflects version 3 of the trial manuscript, dated 10/12/2020.